The impact of COVID-19 pandemic on rabies post-exposure prophylaxis services in Asia. Issue 5 (30th November 2022) - Gongal, Gyanendra; Sampath, Gadey; Kishore, Jugal; Bastola, Anup; Punrin, Suda; Gunesekera, Amila
ABSTRACT: Human rabies is a preventable disease through post-exposure prophylaxis (PEP) in rabies endemic countries where enzootic cycle of dog rabies occurs. The COVID‑19 pandemic has induced an unprecedented challenge for under-funded and already stretched health‑care systems particularly in low- and middle-income countries, which are unfortunately bearing a huge burden of human rabies. An analysis of hospital-based PEP data in India, Nepal, Sri Lanka, and Thailand, focus group discussion and key informant interview have been carried out to better understand the impact of Covid-19 pandemic in human rabies prophylaxis. It is necessary to better prepare for human rabies prophylaxis in future pandemics based on lesson learnt from current pandemic. The PEP should be categorized as an emergency medical service, and it should be part of the hospital medical emergency. Mass dog vaccination against rabies should be accelerated to reduce the risk of potential bite of roaming dogs and pet dogs in communities. It is a wise decision to invest in cost-effective preparedness, i.e., mass dog vaccination rather than costly response, i.e., human rabies prophylaxis.